2022
DOI: 10.1038/s41598-022-05179-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and TMS-related EEG changes as new biomarkers to measure anti-epileptic drug effects

Abstract: Robust biomarkers for anti-epileptic drugs (AEDs) activity in the human brain are essential to increase the probability of successful drug development. The frequency analysis of electroencephalographic (EEG) activity, either spontaneous or evoked by transcranial magnetic stimulation (TMS-EEG) can provide cortical readouts for AEDs. However, a systematic evaluation of the effect of AEDs on spontaneous oscillations and TMS-related spectral perturbation (TRSP) has not yet been provided. We studied the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…It is possible that, as for M1, different neuronal populations can be activated in the pre–SMA by varying CO and SI; however, investigating this outside M1 is difficult due to the absence of a direct readout such as MEP. This problem can be solved with the use of combined TMS and electroencephalography (TMS–EEG), which allows to record postsynaptic potentials generated by the magnetic pulse in the form of transcranial evoked potentials (TEPs) [ 7 , 18 , 19 , 20 ] or oscillations [ 21 , 22 ], and, thus, to have a readout from cortical areas outside M1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that, as for M1, different neuronal populations can be activated in the pre–SMA by varying CO and SI; however, investigating this outside M1 is difficult due to the absence of a direct readout such as MEP. This problem can be solved with the use of combined TMS and electroencephalography (TMS–EEG), which allows to record postsynaptic potentials generated by the magnetic pulse in the form of transcranial evoked potentials (TEPs) [ 7 , 18 , 19 , 20 ] or oscillations [ 21 , 22 ], and, thus, to have a readout from cortical areas outside M1.…”
Section: Introductionmentioning
confidence: 99%
“…To assess cortical excitability, we analysed TEPs in terms of discrete peaks and local mean field potential (LMFP), a reference–free measure commonly used to measure local excitability of a specific area, from a cluster of nearby electrodes [ 6 , 23 , 24 ]. To assess cortical oscillations, we computed TMS–related spectral perturbation (TRSP), a measure reflecting the power of TMS–evoked response in the frequency domain [ 21 , 22 , 24 ]. These variables were computed locally to the SMA since we were interested in the response of this area obtained with three different SIs (100%, 120% and 140%) of resting motor threshold (RMT) and four different COs (0°, 90°, 180° and 270°, starting with the coil handle pointing posteriorly on the transverse plane and proceeding counterclockwise).…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that 20 mg of XEN1101 reduced cortical and corticospinal excitability, similar to other AEDs. These findings suggest that TMS can be a valuable tool for informing early-stage clinical trials 9 .…”
mentioning
confidence: 86%
“…Nonetheless, adequate masking of the auditory evoked potential (AEP) facilitates evaluation of delayed cortical responses to the magnetic field (ter Braack et al, 2015 ), supporting their application as supplementary markers of cortical excitability, both locally and on global scales (Du et al, 2017 ; Roos et al, 2021 ). Investigation of TIO allows the characterisation of rhythmic changes to TMS and can be employed as markers of response to anti‐seizure medications (Biondi et al, 2022 ). Interestingly, early phase synchronisation was found to be linearly dependent on stimulation intensities thus offering an attractive alternative to conventional EMG based cortical excitability markers that may be flawed by spinal excitability (Saari et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%